2023
DOI: 10.1002/cnma.202300140
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth‐Based Oxide Photocatalysts for Selective Oxidation Transformations of Organic Compounds

Abstract: Selective oxidation of organic compounds is incredibly important in the production of a broad range of important chemicals. As such, these reactions attract a great deal of research attention, particularly where conventional synthesis uses harsh and corrosive reaction conditions. To decrease energy consumption, improve yields and mitigate environmental impacts, heterogeneous photocatalysis has emerged as a green and facile method, where its attractiveness is due to promises of providing low toxicity and low‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…Among the current strategies, semiconductor photocatalysis is considered a promising and sustainable solution because it uses limitless solar light as the input energy source and does not require harsh temperature and pressure conditions. [2][3][4][5][6][7][8][9][10] In addition, in photocatalytic NO removal, simultaneous toxic NO 2 conversion and green product (NO 3 − ) selectivity are also worth considering along with the NO removal efficiency. 11,12 Hence, it is vital to nd a promising catalyst system that can meet these requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Among the current strategies, semiconductor photocatalysis is considered a promising and sustainable solution because it uses limitless solar light as the input energy source and does not require harsh temperature and pressure conditions. [2][3][4][5][6][7][8][9][10] In addition, in photocatalytic NO removal, simultaneous toxic NO 2 conversion and green product (NO 3 − ) selectivity are also worth considering along with the NO removal efficiency. 11,12 Hence, it is vital to nd a promising catalyst system that can meet these requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In that vein, plasmonic photocatalysis has emerged as a promising approach in which photons are used as means to tune the catalytic activity. ,, In this approach, nanostructures built on light-absorbing plasmonic metal nanostructures (PMNs) are used as catalysts. The PMNs (e.g., Ag, Au, and Cu) exhibit an optical phenomenon called plasmonic Mie resonance that is typically in the visible and infrared regions of the electromagnetic spectrum. ,,, At plasmonic Mie resonance frequencies, there is a significant enhancement in the light–matter interaction, resulting in the generation of high electric fields as well as absorption (i.e., excited electron–hole pairs) and scattering in/from the nanostructures. , Numerous reports in the past decade have shown that the energetic charge carriers created in the PMNs can be utilized to control and tune the catalytic activity. ,, However, the reports on the demonstration of tunable product selectivity toward the desired chemical reaction pathway are rather limited, , and it remains a challenge in the field to rationally design and demonstrate tunable selectivity on PMN-based catalysts. , Also, major disagreements and controversies have emerged in recent years on distinguishing the desired plasmonic Mie resonance-mediated electronic and electromagnetic field effects in photocatalysis from the undesired light-induced heating effect. The main reason for this issue is that most of the temperature measurements reported on the plasmonic Mie resonator catalysts are based on macroscopic and ensemble measurements. , To alleviate this issue, local temperature measurement using a nanothermometry technique on a single particle level is desired. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this physical disposal method is affected by the environment and cannot completely decompose or remove waste [ 8 , 9 , 10 ]. Photocatalytic oxidation is considered an emerging technology used to remove organic pollutants [ 3 , 11 , 12 ]. For example, crosslinked gelatin/CuS/PVA nanocomposites have proven to be effective and convenient photocatalysts for removing RhB dye from wastewater under solar irradiation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%